Redesain Visual Identity Azyanu Batik - Hidayatul Hasanah; Fauzan Aulia (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
Azyanu Batik is an MSME engaged in the field of batik art based on local Minangkabau culture with "1000 Rumah Gadang" batik motifs which was founded by Zulmi Aryani since 2021, having its address at Muara Labuh, Solok Selatan Regency, West Sumatra Province. In this case, Azyanu Batik already has a visual identity but has not applied design principles and logo criteria to the fullest. The purpose of this design is to redesign Azyanu Batik's visual identity by applying design principles and good logo criteria as an effort to increase brand awareness and Azyanu Batik's image. The design method used is the 4D method, consisting of 4 stages, namely Define, Design, Develop, and Disseminate. While the design analysis used is through SWOT analysis. Azyanu Batik's visual identity redesign will be implemented into the main media and applicable media that can support the effectiveness of the visual identity created.